2010
DOI: 10.1111/j.1439-0531.2010.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Herbal Preparation on Libido and Semen Quality in Boars

Abstract: The objective of this study was to investigate the effects of a preparation from herbal extracts (PHE) on libido and semen quality in breeding artificial insemination boars. Ten fertile boars were divided into control and experimental groups according to significant difference of libido. There were no differences in semen quality between groups. Animals were fed a commercial feeding mixture for boars. The feeding mixture for the experimental group was enriched with PHE, which was prepared from Eurycoma longifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
0
13
0
3
Order By: Relevance
“…Semen was collected using an AV and a dummy oestrous female to trigger mating behaviour at 3, 6 and 24 h after treatment injection. Sexual interests were recorded for libido scoring, which is detailed in Table (Frydrychova et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Semen was collected using an AV and a dummy oestrous female to trigger mating behaviour at 3, 6 and 24 h after treatment injection. Sexual interests were recorded for libido scoring, which is detailed in Table (Frydrychova et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Frydrychová et al. () fed boars with a preparation containing extracts of three herbs, including TT , for 10 weeks. All boars had normal semen parameters at the onset of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory animal studies show that root extract enhances sexual characteristics and performance in rodents (22)(23)(24)(25). In a study involving a boar model, it was found that E longifolia root extract-treated boars increased sperm counts and semen volume; the effect was attributed to increased level of plasma testosterone (26). Reports also suggest that E longifolia extract reverses the inhibitory effects of estrogen on testosterone production and spermatogenesis in rats (27).…”
Section: E Longifolia Jack (Tongkat Ali)mentioning
confidence: 99%